2019
DOI: 10.3390/ma12142301
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorene Is the New Graphene in Biomedical Applications

Abstract: Nowadays, the research of smart materials is focusing on the allotropics, which have specific characteristics that are useful in several areas, including biomedical applications. In recent years, graphene has revealed interesting antibacterial and physical peculiarities, but it has also shown limitations. Black phosphorus has structural and biochemical properties that make it ideal for biomedical applications: 2D sheets of black phosphorus are called Black Phosphorene (BP), and it could replace graphene in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…−346.7 kJ/mole. Considering the interaction of spike protein deformed by phosphorene and graphene with ACE2, it is understood that the performance of all these nanomaterials is similar; however, because of the lower biodegradability in vivo and higher cytotoxicity of graphene, phosphorene has priority in the biological environments [52]. Moreover, oxygen exerts dissociating effects on the phosphorene nanomaterials [84].…”
Section: Evaluation Of the Interaction Of Sars-cov-2 Spike Protein With Ace2 Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…−346.7 kJ/mole. Considering the interaction of spike protein deformed by phosphorene and graphene with ACE2, it is understood that the performance of all these nanomaterials is similar; however, because of the lower biodegradability in vivo and higher cytotoxicity of graphene, phosphorene has priority in the biological environments [52]. Moreover, oxygen exerts dissociating effects on the phosphorene nanomaterials [84].…”
Section: Evaluation Of the Interaction Of Sars-cov-2 Spike Protein With Ace2 Receptormentioning
confidence: 99%
“…These 2D nanomaterials include different families where graphene and its derivatives are very well-known [50,51]. Phosphorene has also been introduced as a new class of biocompatible alternative for graphene in medical science [52,53]. For example, Zhang et al [53] reported better performance of graphene compared to the phosphorene in the disruption of villin headpiece (HP35) function.…”
Section: Introductionmentioning
confidence: 99%
“…-346.7 kJ/mole. Considering the interaction of spike proteins deformed by phosphorene and graphene with ACE2, it is understood that the performance of all these nanosheets is similar; however, because of the lower biodegradability in vivo and higher cytotoxicity of graphene, phosphorene have priority in the biological environments [52]. Moreover, oxygen exerts dissociating effects on the phosphorene nanosheet [85].…”
Section: Evaluation Of the Interaction Of Sars-cov-2 Spike Proteins With Ace2 Receptormentioning
confidence: 99%
“…These materials include different families where graphene and its derivatives are very well-known [50,51]. Phosphorene has also been introduced as a new class of biocompatible alternative for graphene in medical science [52,53]. For example, Zhang et al reported better performance of phosphorene compared to the graphene in the disruption of villin headpiece (HP35) function [53].…”
Section: Introductionmentioning
confidence: 99%
“…As far as biomedical applications are concerned, 2D nanomaterials are promising in optical imaging, biosensing, phototherapy, targeted delivery, and other fields [51][52][53][54][55][56][57]. The tunable band gap of phosphorene, which is size-dependent, allows its interaction with the electromagnetic field to be manipulated in a layer-dependent manner, in the ultraviolet (UV) and near-infrared (NIR) regions.…”
Section: Biomedical Applicationsmentioning
confidence: 99%